BHAR: a bidirectional hierarchy-based anycast routing protocol for wireless sensor networks. (1st January 2014) - Chuang, Po-Jen; Hu, Teng-Tai
This paper presents a bidirectional hierarchy-based anycast routing (BHAR) protocol to facilitate data collection in multi-hop wireless sensor networks (WSNs). In contrast to existing HAR mechanisms (Thepvilojanapong et al., 2005), the proposed BHAR is able to prolong network lifetime as it constructs hierarchical trees and repairs routes faster. BHAR is unique in letting sinks and sources initialise the construction of a hierarchical tree. Whenever a node knows its own parent and neighbour nodes, it can join a tree, exchange/refresh the routing table, and perform route repair without the aid of geographical information or being controlled remotely. As simulation results have demonstrated, such a design makes BHAR a faster and better protocol in constructing trees and repairing routes than HAR.